Pengaruh Audit Internal dan Good Corporate Governance terhadap Kinerja Keuangan Perbankan Syariah - Fauziah Fitri; Mayar Afriyenti (Universitas Negeri Padang, 2021)
The aim of this study was to analyze the influence of internal audit and good corporate governance on financial performance of islamic banking in Indonesia. The data used in this study are annual reports of islamic banking listed on the Financial Services Authority (OJK) in the period 2014-2019. The method of taking data samples using purposive sampling method. Based on this method, a sample of 66 observations was obtained. Hypothesis testing in this study uses multiple linear regression analysis. The result show that internal audit has a positive and significant effect on financial performance, the board of directors has a positive but insignificant effect on financial performance, the board of commissioners has a negative and insignificant effect on financial performance, the audit committee has a positive and significant effect on financial performance, and the shariah supervisory board has a negative and insignificant effect on financial performance.